The rhythm of the murga portena in the eternal city: Roman murga or Argentinian murga? - Liffredo, Florencia (Romanica Olomucensia, 2015)
The murga is the typical expression of the Argentinian carnival: it is a combination of dance, percussion and vocals, which expresses both a form of street art and a form of social criticism. The first ``Argentinian'' murga in Rome, called Sin Permiso, was organised in 2002. It was created by Argentinian citizens living in Rome, who met up in the Centro Sociale Occupato Autogestito, a centre of alternative culture in Italy. Over time, the Sin Permiso murga split up, giving birth to different murgas in the city. These were mostly Italians and a few Argentinians and gained a central place within the Roman counterculture scene and the mobilizations against neoliberalism. Today, this phenomenon is expanding in other Italian regions. In this article an explanation will be given of how, thanks to the strong Italian participation and their political and cultural implications, they are starting to be called ``Roman murgas''. At the same time they are becoming a reality in Rome, as both an artistic and a social form of expression.
Keywords: murga; migration; Rome; Argentina; counterculture.